The Manifestation of Religion in the Public Sphere: A Contemporary Debate - Okolo, Ekenedilichukwu A. (Journal of religion and human relations, 2020)
Religion is ever present with human being. This is because man from his origin is seen to be incurably religious; hence he is addressed as homo-religiosus. It is important to note that with the advancement of technology and the development of the society, some scholars tend to posit that religion in no distant time will give way to secularization, but despite the rate of secularization in Europe and other western societies, religion still plays a vital and prominent role to human being. This work will be studied sociologically and will adopt the theory of crossing and dwelling. This is because religion is not a stagnant phenomenon but crosses and cuts across every facet of life. The paper therefore observes that religion is not only relevant to human being but it maintains a prominent position in the public sphere. It also finds that man is a religious animal and as long as he exists, religion will exist. The paper concludes that religion gives ultimate answers to ultimate questions which neither science nor philosophy has answered. Therefore its place in human being and society cannot be done away with as long as man exists.